TRADITIONAL CULINARY SCARCITY AS TOURISM SUPPLY FROM A CULTURAL PERSPECTIVE: A CASE STUDY OF GUDEG MANGGAR IN BANTUL REGENCY - Lisadewi, Isna; Priyambodo, Tri Kuntoro (Sekolah Tinggi Pariwisata Sahid Surakarta, 2024)
Gudeg manggar is known to be one of the traditional foods of interest in Bantul Regency. Gudeg manggar is also known to be unique due to its rarity, making it a culinary with a higher value than other culinary delights. This research aims to find causes of the scarcity of gudeg manggar as a culinary tourism supply. This research used a qualitative method with semi-structured interviews with three gudeg manggar producers. The results show that the scarcity of gudeg manggar as a culinary tourism supply in Bantul Regency occurs due to several factors. Natural factors are often used in answering the availability of ingredients. However, it is not the only cause; cultural factors in the community cause raw materials to become scarce and more valuable. This research can be a consideration in determining how gudeg manggar is marketed as culinary tourism in Bantul Regency.